Scaling down contact length in complementary carbon nanotube field-effect transistors. Issue 27 (30th June 2017) - Liu, Lijun; Qiu, Chenguang; Zhong, Donglai; Si, Jia; Zhang, Zhiyong; Peng, Lian-Mao
Abstract : This paper presents a systematic exploration on source/drain contact length scaling in carbon nanotube complementary FETs based on transfer length method. Abstract : We performed an experimental investigation on contact length ( L c ) scaling of carbon nanotube (CNT) complementary field-effect transistors (FETs). Contact resistances of Sc-contacted (for n-type) and Pd-contacted (for p-type) CNT FETs are respectively retrieved based on the experimental data through the transfer length method (TLM). The performance of L c scaling of Sc/CNT is proved to be comparable to that of the Pd/CNT contact with L c larger than approximately 40 nm, but it degrades sharply when further scaling down L c mainly owing to the surface oxidation of the Sc film. After decoupling the effect of oxide thickness, the intrinsic contact scaling behavior of Sc-contacted CNT FETs is found to be as good as that of the Pd-contacted ones, which can further satisfy the requirement of developing complementary CNT FET technology scaled down to the 14 nm node.